2017
DOI: 10.1158/2326-6066.cir-16-0141
|View full text |Cite
|
Sign up to set email alerts
|

Serine Proteases Enhance Immunogenic Antigen Presentation on Lung Cancer Cells

Abstract: Immunotherapies targeting immune checkpoints have proven efficacious in reducing the burden of lung cancer in patients; however, the antigenic targets of these re-invigorated T cells remain poorly defined. Lung cancer tumors contain tumor-associated macrophages (TAM) and neutrophils, which release the serine proteases neutrophil elastase (NE) and proteinase 3 (P3) into the tumor microenvironment. NE and P3 shape the antitumor adaptive immune response in breast cancer and melanoma. In this report, we demonstrat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 43 publications
(67 reference statements)
2
20
0
Order By: Relevance
“…Furthermore, we note that fine epitope mapping demonstrated that 8F4 has contact residues with the HLA-A2 molecule (13). As HLA-A2 is part of the conformational epitope of PR1/ HLA-A2, naturally we expect some binding of 8F4 to HLA-A2, as shown previously (14,15,19). However, to date, preclinical studies (13,26) and clinical trials (11,32) have demonstrated PR1-targeting immunotherapies to be safe and efficacious despite the shared expression of NE and P3 between malignant cells and normal counterpart, and the binding of 8F4 to HLA-A2.…”
Section: Discussionsupporting
confidence: 76%
See 3 more Smart Citations
“…Furthermore, we note that fine epitope mapping demonstrated that 8F4 has contact residues with the HLA-A2 molecule (13). As HLA-A2 is part of the conformational epitope of PR1/ HLA-A2, naturally we expect some binding of 8F4 to HLA-A2, as shown previously (14,15,19). However, to date, preclinical studies (13,26) and clinical trials (11,32) have demonstrated PR1-targeting immunotherapies to be safe and efficacious despite the shared expression of NE and P3 between malignant cells and normal counterpart, and the binding of 8F4 to HLA-A2.…”
Section: Discussionsupporting
confidence: 76%
“…S2). Previously, we demonstrated that solid tumor cells can cross-present PR1 from both soluble and cell-associated sources of NE and P3 (14,19). These findings were recapitulated in the U266 multiple myeloma cells that were cocultured with soluble NE, P3, or irradiated HLA-A2 À PMNs, the latter serving as the cellular source of NE and P3 that lack endogenous PR1 ( Fig.…”
Section: Hla-a2 þ Multiple Myeloma Cells Take Up and Cross-present Nesupporting
confidence: 55%
See 2 more Smart Citations
“…Moreover, it has been found that PRTN3 induces phosphorylation and nuclear translocation of p44/ p42 and JNK1, leading to cancer cell motility, through a nonproteolytic way [19]. Notably, recent studies revealed that PRTN3 expressed by neutrophils within the TME can be taken up by breast cancer and melanoma cells, which in turn increase the susceptibility to PR1-targeting therapies [14,20].…”
Section: Introductionmentioning
confidence: 99%